Black Panther : a nation under our feet. Book one - Coates, Ta-Nehisi.; Stelfreeze, Brian; Lee, Stan, 1922-; Kirby, Jack. (New York, NY : Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2016)
"T'Challa confronts a dramatic upheaval in Wakanda that will make leading the African nation tougher than ever before! When a superhuman terrorist group calling itself The People sparks a violent uprising, the land famed for its incredible technology and proud warrior traditions will be thrown into turmoil. As suicide bombers terrorize the population, T'Challa struggles to reunite his ciizens, and a familiar villain steps out of the shadows. If Wakanda is to survive, it must adapt--but can its monarch, one in a long line of Black Panthers, survive the necessary change? Heavy hangs the head that wears the cowl!"--Back cover.
"Contains material originally published in magazine form as Black Panther #1-4 and Fantastic Four #52."
"Black Panter created by Stan Lee & Jack Kirby."
"Collected Editions"--Inside front cover.
"T"--Back cover.
Library Journal Starred, November 2016
Booklist, November 2016
Keywords: Black Panther -- (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Kings and rulers -- Africa -- Comic books, strips, etc. -- Juvenile fiction; Superheroes -- Comic books, strips, etc. -- Juvenile fiction; Africa -- Comic books, strips, etc. -- Juvenile fiction; Black Panther -- (Fictitious character) -- Fiction; Kings, queens, rulers, etc. -- Fiction; Superheroes -- Fiction; Africa -- Fiction; Black Panther -- (Fictitious character) -- Comic books, strips, etc. -- Fiction; Kings and rulers -- Comic books, strips, etc. -- Fiction; Superheroes -- Comic books, strips, etc. -- Fiction; Africa -- Comic books, strips, etc. -- Fiction; Superhero comics; Graphic novels